THE IMPRESCRIPTIBILITY OF CRIMES AGAINST FREEDOM AND SEXUAL INDEMNITY IN PERU - Sáenz Torres, Alexei Dante (2019)
The purpose of this article is to analyze the positive and negative aspects of Law N ° 30838, by means of which the imprescriptibility of crimes against sexual freedom, sexual indemnity and other related crimes was incorporated for the first time into the 1991 Penal Code. How to establish the scope of the reform in the Peruvian penal system.